Candidate genes involved in the evolution of viviparity: a RAD sequencing experiment in the lizard Zootoca vivipara (Squamata: Lacertidae). Issue 1 (19th October 2017) - Cornetti, Luca; Griffith, Oliver W; Benazzo, Andrea; Panziera, Alex; Whittington, Camilla M; Thompson, Michael B; Vernesi, Cristiano; Bertorelle, Giorgio
Abstract: Viviparity has evolved from oviparity at least 150 independent times in vertebrates. More than 80% of these transitions have occurred in squamate reptiles, where both reproductive modes are rarely seen in different populations of the same species. This condition (bimodal reproduction) is ideal for studying the physiological and morphological changes underpinning the evolution of reproductive mode, and their genetic determinants. Here we analysed the genomes of Zootoca vivipara populations with either oviparous or viviparous reproduction using a RAD sequencing approach. No signature of interbreeding between oviparous and viviparous individuals was found. We conservatively identified 22 annotated coding sequences in genes potentially associated with parity mode differences. Six of these genes are transcription regulators that are also expressed in reproductive tissues of mammals and reptiles, suggesting that changes in gene expression are important for the evolution of viviparity. Using a more inclusive approach based on contigs mapping in either coding or non-coding regions, 45 genes were identified. Twelve of these candidate genes are transcription regulators and four encode protease enzymes. We propose that the evolution of proteases may support morphological changes to the uterus during pregnancy. This study provides the foundation for further experimental studies of the genetic basis of parity mode in Z. vivipara .